Cryoprecipitate Augments the Global Transduction of the Adeno-Associated Virus Serotype 9 After a Systemic Administration - Chai, Zheng (J Control Release, 2018)
Adeno-associated virus (AAV) vectors have been successfully used for transgene delivery in clinical trials. A systemic administration of AAV vectors has been proposed in order to achieve global transduction, which requires that the AAV vector is capable of crossing the blood vessels. It has been demonstrated that serum proteins are able to directly interact with AAV virions to enhance liver transduction. In this study, we investigate whether the serum proteins have the potential to increase the capacity of AAV to diffuse through the endothelial cells and deliver the transgene into the whole body. First, we found that the direct interaction of serum with AAV9 virions increased the epithelial cell permeability of AAV9 in vitro. Several serum proteins with a potential effect on AAV vascular permeability have been identified from mass spectrometry analysis, including fibrinogen, fibronectin, von Willebrand factor (vWF), platelet factor 4, alpha-1-acid glycoprotein, and plasminogen. The incubation of these serum proteins with AAV9 enhanced the global transduction in mice after a systemic administration. To apply these findings in clinical practice, we demonstrated that the clinical product cryoprecipitate (mainly containing fibrinogen and vWF) augmented AAV9 global transduction. The mechanism study revealed that cryoprecipitate slowed down the clearance of AAV9 vectors in the blood so that the AAV9 vectors had sufficient time to travel to the peripheral organs. In summary, the results from this study suggests that serum proteins interact with AAV virions and enhance the AAV9 vascular permeability for global transduction, and, more importantly, cryoprecipitate can be immediately applied for clinical patients who need the systemic administration of AAV vectors for global transduction.